The Effect of the Index Card Match Learning Model on the Learning Outcomes of Class V PKn - Saut Mardame Simamora; Wirda Budia Khaira (Edumaspul: Jurnal Pendidikan, 2024)
This research aims to determine whether students' learning outcomes in class V in the Civics subject at SD IT Permata Medan Labuhan are influenced by the Active Learning Model of the Index Card Match Type. There are two hypotheses in this research, namely: (1) There is an influence of the Index Card Match Type Active Learning Model on student learning outcomes in class V in Civics subjects at SD IT Permata Medan Labuhan (Ha), and (2) There is no influence of the Learning Model Active Index Card Match Type on student learning outcomes in class V Civics subjects at SD IT Permata Medan Labuhan (Ho). This research uses an experimental method with a pre-experimental research type with a "One Group Pretest Posttest Design." The data was tested using analysis assisted by SPSS Version 26, and the results were the average pretest (44.00) and average posttest (86.50). According to data analysis of pretest and posttest scores, research results at the 0.5 level show that the sig (2-tailed) value is 0.00 <0.05, which indicates that Ho is rejected and Ha is accepted. Thus, it can be concluded that the Index Card Match learning model in Civics subjects in class V of SD IT Permata Medan Labuhan significantly impacts student learning outcomes.